2008 Digital Image Computing: Techniques and Applications 2008
DOI: 10.1109/dicta.2008.13
|View full text |Cite
|
Sign up to set email alerts
|

Facial Expression Recognition Using Neural Networks and Log-Gabor Filters

Abstract: This study proposes a classification-based facial expression recognition method using a bank of multilayer perceptron neural networks. Six different facial expressions were considered. Firstly, logarithmic Gabor filters were applied to extract the features. Optimal subsets of features were then selected for each expression, down-sampled and further reduced in size via Principal Component Analysis (PCA). The arrays of eigenvectors were multiplied by the original log-Gabor features to form feature arrays concate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 19 publications
(16 reference statements)
1
8
0
Order By: Relevance
“…Based upon those results, it can be concluded that the accuracy of emotion recognition of the developed system is in line with those from other sources where a lot more samples were used in the creation and learning process, as in [9], [12] and [17]. Due to the difference between the databases used, a detailed comparison with those developed systems requires a more rigorous comparative analysis.…”
Section: Fig 5 Confusion Table Chartsupporting
confidence: 68%
See 1 more Smart Citation
“…Based upon those results, it can be concluded that the accuracy of emotion recognition of the developed system is in line with those from other sources where a lot more samples were used in the creation and learning process, as in [9], [12] and [17]. Due to the difference between the databases used, a detailed comparison with those developed systems requires a more rigorous comparative analysis.…”
Section: Fig 5 Confusion Table Chartsupporting
confidence: 68%
“…Generally, when considering emotion recognition from static images there are two basic principles that determine which facial region is going to be used for feature extraction. In one principle, the face is globally analyzed and features from the entire face are gathered as in [9] and [17], while according to the second principle, analysis is employed on only certain facial regions of which we know that they hold information about emotions, i.e. regions like the mouth, eyes or eyebrows.…”
Section: Static Image Analysismentioning
confidence: 99%
“…The singularity of the log function Log Gabor filters basically are defined in the frequency domain as Gaussian functions that shift from the origin [17]. Gabor filters present a limitation in the bandwidth where only bandwidth of 1 octave maximum could be designed [18][19][20]. Log Gabor consists of a logarithmic transformation in the Gabor domain which eliminates the DC-component allocated in medium and high-pass filters.…”
Section: 13log Gabor Filtermentioning
confidence: 99%
“…The Gabor wavelet employs multi-channel and multi-layer methods to capture facial features while simultaneously effectively identifying skin surface topographies of different frequencies on human faces. It can also be used in classifying facial expressions [9] [10]. Gabor Wavelet is defined as:…”
Section: B Log-gabor Waveletmentioning
confidence: 99%
“…The Gabor wavelet is mainly used in face recognition systems to capture frequency information from facial features [5][7] [9][10] [11]. The Gabor wavelet employs multi-channel and multi-layer methods to capture facial features while simultaneously effectively identifying skin surface topographies of different frequencies on human faces.…”
Section: B Log-gabor Waveletmentioning
confidence: 99%